Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In page 53 of Arieh Iserles's A first course in the numerical analysis of differential equations, he presents the following ODE:

$(\vec{y})'=\Gamma\cdot\vec{y}$,

$\vec{y}(0)=\vec{y_0}$

Using the fact that the spectral factorization of $\Gamma$ gives us $\Gamma=VDV^{-1}$, where $D$ is the diagonal matrix containing the eigenvalues and $V$ is the corresponding eigenvector matrix, he deduces (without working) that the exact solution of the ODE is: $\vec{y}(t)=e^{t\Gamma} = Ve^{tD}V^{-1}\vec{y_0}$

  1. In order to get $\vec{y}(t)=e^{t\Gamma}$ it looks like he did: $\displaystyle \int \frac{(\vec{y})'}{\vec{y}} dt = \int \Gamma dt$. But how can he do this when $\vec{y}$ is a vector?

  2. Using the spectral factorization, $e^{t\Gamma} = e^{tVDV^{-1}}$. How did he get $Ve^{tD}V^{-1}\vec{y_0}$ from this?

share|improve this question
1  
You have several answers now. Any comments or questions on any of them? –  Gerry Myerson Apr 29 at 13:13
1  
Yeah, apologies for the late reply, was very preoccupied with work today. I've just asked a question regarding one of them. Don't worry about me leaving the question open; I always accept an answer. –  Twilight Sparkle Apr 29 at 13:30

3 Answers 3

up vote 1 down vote accepted

The answer to the first question I present below was copied from this answer of mine and it works whether the matrix is diagonalizable or not.

Given $n\in \mathbb N, A\in \mathbb R^{n\times n}$, a non trivial interval $I, t_0\in I, y_0\in \mathbb R^n$ and $b\colon I\to \mathbb R^n$ a continuous function, consider the initial value problem $$y'+Ay=b, y(t_0)=y_0.$$

Let $f\colon I\to\mathbb R^n$ be a differentiable function.

Fact: For all $t\in \mathbb R$, $e^{At}$ is invertible and $\left(e^{At}\right)^{-1}=e^{-At}$.

There exists $C\in \mathbb R^n$ such that for all $t\in I$ the following holds: $$\begin{align} f'(t)+Af(t)=b(t)&\iff e^{At}(f'(t)+Af(t))=e^{At}b(t)\\ &\iff e^{At}f'(t)+e^{At}Af(t)=e^{At}b(t)\\ &\iff e^{At}f'(t)+Ae^{At}f(t)=e^{At}b(t)\\ &\iff \int \limits _{t_0}^te^{As}f'(s)+Ae^{As}f(s)\mathrm ds=\int \limits_{t_0}^te^{As}b(s)\mathrm ds+C\\ &\iff e^{At}f(t)=\int \limits_{t_0}^te^{As}b(s)\mathrm ds+C\\ &\iff f(t)=e^{-At}\int \limits_{t_0}^te^{As}b(s)\mathrm ds+e^{-At}C. \end{align}$$

Taking into account $f(t_0)=y_0$ after some simple calculations it follows that $C=e^{At_0}y_0$.


As for the second question, just use the definition of matrix exponential together with what was done above: $$\begin{align} e^{t\Gamma }&=\sum \limits_{n=0}^\infty\left(\dfrac {t^n} {n!}\Gamma^n\right)\\ &=\sum \limits_{n=0}^\infty\left(\dfrac {t^n} {n!}\left(VDV^{-1}\right)^n\right) \\ &=\sum \limits_{n=0}^\infty\left(\dfrac {t^n} {n!}VD^nV^{-1}\right)\\ &=V\sum \limits_{n=0}^\infty\left(\dfrac {t^n} {n!}D^n\right)V^{-1}\\ &=Ve^{tD}V^{-1}. \end{align}$$

share|improve this answer
    
Hi! Sorry if this is a silly question, but how did you manage to shift the A in $e^{At}A$ to $Ae^{At}$? –  Twilight Sparkle Apr 29 at 13:31
1  
@TwilightSparkle $$\forall t\in \mathbb R\left[e^{At}A=\sum \limits_{n=0}^\infty\left(\dfrac 1{n!}A^n\right)A=\sum \limits_{n=0}^\infty\left(\dfrac 1{n!}A^{n+1}\right)=A\sum \limits_{n=0}^\infty\left(\dfrac 1{n!}A^n\right)\right].$$ –  Git Gud Apr 29 at 13:34

It looks like you are confused by the formal procedure... don't write $\int \frac{(\vec{y})'}{\vec{y}}dt=\int \Gamma dt$, it doesn't make a lot of sense in this form unless you really specify what you mean by any of the operations here.

It's much simpler than that. You can imagine substituting $\vec{w}=V^{-1}\vec{v}$. Now, your set of differential equations reads as

$$(\vec{w})'=D\vec{w}$$

Because $D$ is diagonal, the components are not coupled and the above is a set of $n$ independent differential equation, which can each be integrated separately.

Additionally, it's perfectly fine to solve by Ansatz without integration, in which case you don't get have ambiguous expression.

share|improve this answer

Let $y=Vu$. Then $y'=Vu'$, but also $y'=\Gamma y=\Gamma Vu$, so $Vu'=\Gamma Vu$, so $u'=V^{-1}\Gamma Vu=Du$. Since $D$ is diagonal we can solve this: $u=e^{tD}u_0$. That's $y=Vu=Ve^{tD}u_0=Ve^{tD}V^{-1}y_0$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.